Teknik Produksi Naupli Udang Vaname (Litopenaeus vannamei) di Hatchery CV. Pacific Andre Anton (PAA) Kabupaten Situbondo Provinsi Jawa Timur - Ardiansyah Maulana Ahmad; Teguh Harijono; Kartika Primasari (JURNAL RISET RUMPUN ILMU HEWANI, 2025)
Whiteleg shrimp (Litopenaeus vannamei) is a leading commodity in the aquaculture sector with high economic value. To support shrimp farming productivity, the provision of high-quality seed stock must begin with optimal nauplius production techniques. This study aims to examine the nauplius production process of L. vannamei at the CV. Pacific Andre Anton (PAA) hatchery in Situbondo, East Java, covering stages such as media preparation, broodstock management, spawning, egg hatching, and nauplius harvesting. The methods used were observation, interviews, and active participation during the internship program. Observations revealed that natural spawning was conducted using a male-to-female broodstock ratio of 3:1–5:1, with broodstock aged at least 8 months. Over one month of production, a total of 51,418,901 eggs were produced, with a hatching rate of 87% and nauplius yield reaching 44,954,325. Key success factors in nauplius production include broodstock quality, eyestalk ablation technique, strict water quality management, high-nutrition feeding, and the implementation of biosecurity protocols. The findings indicate that the nauplius production techniques applied at CV. PAA meet established standards and can serve as a reference for developing L. vannamei hatchery operations.